Exploring the Future of Work: Impact of Automation and Artificial Intelligence on Employment - Masriadi; Dasmadi; Nurul Efri Ekaningrum; Muhammad Syahrul Hidayat; Farida Yuliaty (Global Writing Academica Researching & Publishing, 2023)
The presence of Artificial Intelligence (AI) and automation of work provide a revolution in the world of work. But at the same time, this can threaten human potential in employment. This research was conducted to see the influence exerted by AI and automation on human employment. This research will be carried out using a descriptive qualitative approach. The data used in this study comes from various research results and previous studies that still discuss the use of AI and automation in the world of work. This study found that AI and automation are currently replacing many jobs. However, some bits of intelligence belonging to humans, such as intuition and empathy, is still difficult for AI to imitate. Even though the existence of AI and automation can be a threat to humans in the workforce, with the increase in human resource skills; then humans who adapt will not be replaced by machines, but there will be the integration of human-machine work, where AI and automation do not replace humans but become tools for human labor.